Hypertrophic effects of single- versus multi-joint exercise of the limb muscles: a systematic review and meta-analysis - Rosa, A.; Vazquez, G.; Grgic, J.; Balachandran, A. T.; Orazem, J.; Schoenfeld, B. J. (Strength and Conditioning Journal, 2023)
We performed a systematic review and meta-analysis comparing the effects of single-joint (SJ) and multijoint (MJ) resistance exercises on muscle hypertrophy of the limb muscles. A systematic search was performed to identify randomized trials that directly compared hypertrophic changes between SJ and MJ resistance exercises, as well as combinations of the 2, in healthy adults. A total of 7 studies met inclusion criteria, comprising 10 nested comparisons. Meta-analysis indicated a trivial standardized point estimate with a relatively moderate precision for the confidence interval estimate. Subgroup analyses showed no effect on results when stratifying studies according to combined SJ + MJ versus MJ training alone, as well as under volume-equated or nonequated conditions. However, scrutiny of individual studies in conjunction with related indirect evidence collectively indicate that SJ exercise may provide the ability to preferentially hypertrophy muscular subdivisions, potentially promoting more complete muscle development. We conclude that current evidence indicates similar whole muscle hypertrophy between MJ and SJ training. There may be added benefit to combining SJ and MJ exercises for targeting individual aspects of a given muscle, although this hypothesis remains understudied. Future studies are needed to explore the effects of SJ and MJ exercises in resistance training on regional muscle hypertrophy.